Crop breeding : a contemporary basis - Vose, Peter B.; Blixt, S. G. (Stig G.) (Pergamon, 1983)
The aim of this book is to gather together, in an integrated manner, information on the physiology and technology of contemporary plant breeding. The approach is multidisciplinary, with special emphasis being placed on the application of theoretical knowledge to the solution of practical problems concerned with the improvement of crop yield through the breeding of plants better suited to their environment. The role of modern techniques, such as tissue culture and induced mutation are discussed in detail.